Catalytic potential of Singgora roof tiles in transesterification for sustainable biodiesel - NOR FAIZAH BINTI HAMINUDIN, NOR FAIZAH BINTI HAMINUDIN; AHMAD FUAD BIN ABDUL RASID, AHMAD FUAD BIN ABDUL RASID; AMIERA HUSNA BINTI ABDUL HALIM, AMIERA HUSNA BINTI ABDUL HALIM; MAHANUM BINTI MOHD ZAMBERI, MAHANUM BINTI MOHD ZAMBERI; MOHD HAIZAL BIN MOHD HUSIN, MOHD HAIZAL BIN MOHD HUSIN; NORFADHILAH BINTI HAMZAH, NORFADHILAH BINTI HAMZAH (Penerbit Akademia Baru, 2024)
The study centred around the uitilization of Singgora roof tiles as a heterogeneous catalyst in the production of biodiesel via the transesterification process. The motivation behind this choice stems from the non-recyclable nature of Singgora roof tiles and their potential applicability in biodiesel synthesis. To enhance the catalytic properties, zinc oxide (ZnO) is incorporated using the wet impregnation technique during catalyst preparation. The catalyst was characterized by XRF and SEM-EDX. A two-step transesterification method is employed to mitigate the levels of free fatty acid (FFA) in waste cooking oil (WCO). The initial step involves treating the WCO with sulfuric acid (H2SO4) to reduce FFA. Subsequently, the Singgora roof tiles catalyst is utilized in the second step. A high yield of FAMEs, specifically 96.96%, was achieved under the optimal conditions, which included a methanol-to- oil ratio of 12:1, a catalyst concentration of 1 wt.%, a reaction temperature of 65 °C, and a reaction time of 2 hours. The quality of the biodiesel produced was analyzed according to biodiesel standards such as ASTM D6751, EN 14214, and AOCS, and it met all the required standards. The study demonstrates the potential of using Singgora roof tiles as a heterogeneous catalyst in biodiesel production, offering a promising approach to repurposing non-recyclable materials and advancing sustainable biodiesel production methods.